2013
DOI: 10.1016/j.jce.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of economic reforms on manufacturing dualism: Evidence from India

Abstract: This paper forms part of a larger study funded by the Economic and Social Research Council (ESRC), United Kingdom. We are thankful to the ESRC for financial support. We are also thankful to the Central Statistical Organization for providing us access to the data and to Professor William Greene for many suggestions and comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The estimated selection models show that the selection variable RHO (x, v) is statistically significant for non-owners (Table 3), suggesting the presence of selection bias on unobserved variables and lending support to the use of a sample selection framework to estimate separate stochastic ODFs for landowners and non-owners. Moreover, in the presence of selection bias, the use of the conventional method leads to biased estimates of the parameters of the stochastic distance function, which affects the TE score (Kumbhakar et al, 2009;Greene, 2010;Bravo-Ureta et al, 2012;Kathuria et al, 2013). Table 4 shows the TE scores obtained using the estimated stochastic ODF models.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated selection models show that the selection variable RHO (x, v) is statistically significant for non-owners (Table 3), suggesting the presence of selection bias on unobserved variables and lending support to the use of a sample selection framework to estimate separate stochastic ODFs for landowners and non-owners. Moreover, in the presence of selection bias, the use of the conventional method leads to biased estimates of the parameters of the stochastic distance function, which affects the TE score (Kumbhakar et al, 2009;Greene, 2010;Bravo-Ureta et al, 2012;Kathuria et al, 2013). Table 4 shows the TE scores obtained using the estimated stochastic ODF models.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Recent literature on stochastic frontier production (SFP) functions has shown that the choice of production technology could be endogenous. These potential biases need to be taken into account when estimating technical efficiency (TE) scores (Kumbhakar et al, 2009;Greene, 2010;Bravo-Ureta et al, 2012;Wollni and Br€ ummer, 2012;Kathuria et al, 2013). The land property rights of the farmer influence the choice of production technology and vice-versa as shown by Abdulai et al (2011), Besley (1995, Brasselle et al (2002), Place and Otsuka (2001), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions are Kathuria et al . () and Sato () who combine the two types of data. But the comparability of the two types of datasets remains a problem.…”
mentioning
confidence: 99%
“…Even in countries experiencing strong economic growth, the informal sector often remains large and relatively unproductive, pulling down labor productivity and aggregate economic growth (Khaturia et al 2013;De Vries et al 2012). One of the key aspects in understanding the evolution of the informal sector is its interaction with the formal sector (Hart 1973;Weeks 1975;Ranis and Stewart 1999;Davies and Thurlow 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2 A different strand of literature analyzes productivity differences between formal and informal manufacturing in India, showing that informalization of India's economy is slowing down aggregate growth (De Vries et al 2012) and that liberalization reforms in India increased the productivity of formal as well as informal enterprises, but more so for the former (Khaturia et al 2013). 3 In the paper we refer to these as 1995, 2001, and 2006, respectively.…”
mentioning
confidence: 99%